Integrative and Multidisciplinary Care for People Living With Human T-Cell Lymphotropic Virus in Bahia, Brazil: 20 Years of Experience - Galvão-Castro, Bernardo; Grassi, Maria Fernanda Rios; Galvão-Castro, Ana Verena; Nunes, Aidê; Galvão – Barroso, Ana Karina; Araújo, Thessika Hialla Almeida; Rathsam-Pinheiro, Regina Helena; Nunes, Ceuci Lima Xavier; Ribeiro, Adriele; Lírio, Monique; Gonçalves, Noilson Lázaro; Rangel, Sônia Lúcia; et al. (Frontiers in Medicine, 2022)
Brazil is home to the highest absolute number of human T-cell lymphotropic virus type-1 (HTLV-1)-infected individuals worldwide; the city of Salvador, Bahia, has the highest prevalence of HTLV-1 infection in Brazil. Due to the complex nature of several diseases associated with this retrovirus, a multidisciplinary health care approach is necessary to care for people living with HTLV-1. The Bahia School of Medicine and Public Health’s Integrative Multidisciplinary HTLV Center (CHTLV) has been providing support to people living with HTLV and their families since 2002, striving to ensure physical and mental well-being by addressing biopsychosocial aspects, providing clinical care and follow-up, including to pregnant/postpartum women, as well as comprehensive laboratory diagnostics, psychological therapy, and counseling to family members. To date, CHTLV has served a total of 2,169 HTLV-infected patients. The average patient age is 49.8 (SD 15.9) years, 70.3% are female, most are considered low-income and have low levels of education. The majority (98.9%) are HTLV-1 cases, and approximately 10% have been diagnosed with tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM), while 2.2% have infective dermatitis and 1.1% have adult T-cell lymphoma. In all, 178 pregnant/postpartum women [mean age: 32.7 (±6.5) years] have received care at CHTLV. Regarding vertical transmission, 53% of breastfed infants screened for HTLV tested positive in their second year of life, nearly 18 times the rate found in non-breastfed infants. This article documents 20 years of experience in implementing an integrative and multidisciplinary care center for people living with HTLV in Bahia, Brazil. Still, significant challenges remain regarding infection control, and HTLV-infected individuals continue to struggle with the obtainment of equitable and efficient healthcare.